Redefining Well-Being in Nations and Organizations A Process of Active Committed Enthusiasm - Jawad, Ali Qassim; Scott-Jackson, William; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2016)
Redefining Well-Being in Nations and Organizations is an essential book for researchers, policy makers and managers. It provides a new multi-disciplinary perspective on wellbeing and engagement, reviewing the latest research from several previously unrelated disciplines to develop a process for active committed enthusiasm (PACE), encompassing theory and clarifying the definitions of, and relationships between, wellbeing, engagement and related concepts. PACE allows researchers to model causal relationships, and policy makers and managers to analyze the potential impact of possible interventions. It demonstrates that, as nations, organizations and individuals fulfil their basic material needs, the impact of individual optimism, and other aspects of positive psychology, become paramount in maximizing wellbeing and engagement. .
Keywords: Business; Management; Leadership; Organization; Planning; Personnel management; Success in business; Careers; Behavioral economics; Business and Management; Organization; Business Strategy/Leadership.; Management; Behavioral/Experimental Economics; Careers in Business and Mangagement; Human Resource Management; Electronic books